2013
DOI: 10.2967/jnumed.112.113563
|View full text |Cite
|
Sign up to set email alerts
|

First Experience of 18F-Alfatide in Lung Cancer Patients Using a New Lyophilized Kit for Rapid Radiofluorination

Abstract: 18F-FPPRGD2, which was approved for clinical study recently, has favorable properties for integrin targeting and showed potential for antiangiogenic therapy and early response monitoring. However, the time-consuming multiple-step synthesis may limit its widespread applications in the clinic. In this study, we developed a simple lyophilized kit for labeling PRGD2 peptide (18F-AlF-NOTA-PRGD2, denoted as 18F-alfatide) using a fluo-ride–aluminum complex that significantly simplified the labeling procedure. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
178
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(187 citation statements)
references
References 33 publications
3
178
0
3
Order By: Relevance
“…However, only a few clinical PET imaging sites routinely offer 18 F-radiolabeled peptides as a result of the typically difficult radiochemistry involved in peptide labeling with 18 F (10,11). Therefore, new labeling approaches have been developed, especially over the last decade (12)(13)(14)(15)(16). One of these approaches takes advantage of the thermodynamically favored formation of silicon-18 F bonds (silicon-fluoride acceptor [SiFA] chemistry, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few clinical PET imaging sites routinely offer 18 F-radiolabeled peptides as a result of the typically difficult radiochemistry involved in peptide labeling with 18 F (10,11). Therefore, new labeling approaches have been developed, especially over the last decade (12)(13)(14)(15)(16). One of these approaches takes advantage of the thermodynamically favored formation of silicon-18 F bonds (silicon-fluoride acceptor [SiFA] chemistry, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tümör anjiogenezi ile ilişkili olarak aktifleşen endotel hücrelerinde integrin adı verilen moleküllerin ekspresyonu artar. İntegrinlerin görüntülenmesine yönelik F-18 ve Ga-68 ile işaretli çeşitli PET ajanları geliştirilmiş, bu ajanlar kullanılarak akciğer kanserinde anjiogenezin PET ile görüntülenmesine yönelik çalışmalar yapılmıştır (87,88,89). CXCR4 çeşitli solid kanseri türlerinde artmış ekspresyon gösteren, tümörün metastaz yapma potansiyeli ile ilişkili bir kemokin reseptörüdür (90,91).…”
Section: Yeni Pet Radyofarmasötikleriunclassified
“…Angiogenesis is necessary for tumor growth and metastasis, and the integrin αvβ3 receptor plays an important role in promoting, sustaining, and regulating the angiogenesis [62] . In vitro analysis demonstrated that integrin αvβ3 receptor was expressed in 60% of invasive pancreatic ductal carcinomas and would be an excellent target for the early detection of malignant PC [63] .…”
Section: Radiolabeled Rgd Analogsmentioning
confidence: 99%